Extensive polymorphism and chromosomal characteristics of ribosomal DNA in the characid fish Triportheus venezuelensis (Characiformes, Characidae) - Nirchio, Mauro; Oliveira, Claudio [UNESP]; Ferreira, Irani Alves [UNESP]; Granado, Angel; Ron, Ernesto (Sociedade Brasileira de Genética, 2007)
The karyotype and chromosomal characteristics of the characid fish Triportheus venezuelensis were investigated using differential staining techniques (C-banding, Ag-NOR staining) and fluorescent in situ hybridization (FISH) with an 18S rDNA probe. The diploid chromosome number (2n = 52), karyotype composition and sex chromosome determination system of the ZZ/ZW type were the same as previously described in other species of the genus Triportheus. However, extensive variation regarding nucleolus organizer regions (NOR) different from other species was observed. 18S rDNA sequences were distributed on nine chromosome pairs, but the number of chromosomes with Ag-NORs was usually lower, reaching a maximum of four chromosomes. When sequential staining experiments were performed, it was demonstrated that: 1.) active NORs usually corresponded to segments with 18S rDNA genes identified in FISH experiments; 2.) several 18S rDNA sequences were not silver-stained, suggesting that they do not correspond to active NORs; and 3.) some chromosomes with silver-stained regions did not display any 18S rDNA signals. These findings characterize an extensive polymorphism associated with the NOR-bearing chromosomes of T. venezuelensis and emphasize the importance of combining traditional and molecular techniques in chromosome studies.
Keywords: 18S rDNA; Ag-NORs; C-band; FISH; fish cytogenetics; sex chromosomes